A putative redox‐sensing regulator Rex regulates lincomycin biosynthesis in Streptomyces lincolnensis. (27th July 2021) - Hou, Bingbing; Wang, Ruida; Zou, Jingyun; Zhang, Feixue; Wu, Haizhen; Ye, Jiang; Zhang, Huizhan
Abstract: Lincomycin is an important antimicrobial agent which is widely used in clinical and animal husbandry. The biosynthetic pathway of lincomycin comes to light in the past 10 years, however, the regulatory mechanism is still unclear. In this study, a redox‐sensing regulator Rex from Streptomyces lincolnensis (Rexlin ) was identified and characterized to affect cell growth and lincomycin biosynthesis. Disruption of rex resulted in an increase in cell growth, but a decrease in lincomycin production. The results of quantitative real‐time polymerase chain reaction showed that Rexlin can promote transcription of the regulatory gene lmbU and the structural genes lmbA, lmbC, lmbJ, lmbV, and lmbW . However, electrophoretic mobility shift assay analysis demonstrated that Rexlin can not bind to the promoter regions of these genes above. Findings in this study broadened our horizons in the regulatory mechanism of lincomycin production and laid a foundation for strain improvement of antibiotic producers.